PKM AUTOGENIC TRAINING PADA ATLET PETANQUE - Benny Badaru; Ichsani Ichsani; Sudiadarmha Sudiadarmha (KORSAcs: Jurnal Pengabdian Kepada Masyarakat, 2022)
Knowledge and understanding of Autogenic Training is not yet known by the public, especially among athletes. Because Autogenic Training is an unfamiliar term in the ears of athletes. Therefore, through this training and counseling can provide an overview and knowledge of what rules are Autogenic Training and its benefits. This activity is designed into several sub-activities. First, giving an understanding of the personal performance development of Petanque athletes through lectures. Second, giving material about Autogenic Training. Third, the development of Autogenic Training activities with a few examples of activities. Fourth, giving individual tasks that must be done by each participant to develop Autogenic Training for personal performance. The results of the development of this Autogenic Training must be reported to be evaluated so that it can really be used as a guide to conducting a true and ideal Autogenic Training. From the results of the implementation of this activity found the answer that the interest of Petanque athletes in Takalar District to know the additional knowledge of autogenic training with a new term among these athletes is very high, even though in the process of training or competition they get or experience things that are mental pressure in the match. So that their enthusiasm in following the material, both at the time the theory and practice were maintained and never lowered their motivation in participating in the training activities because the training was considered very useful for themselves.